2021
DOI: 10.1038/s41598-021-95773-2
|View full text |Cite
|
Sign up to set email alerts
|

Association between overall diet quality and postmenopausal breast cancer risk in five Finnish cohort studies

Abstract: There is limited evidence for any dietary factor, except alcohol, in breast cancer (BC) risk. Therefore, studies on a whole diet, using diet quality indices, can broaden our insight. We examined associations of the Nordic Diet (mNDI), Mediterranean diet (mMEDI) and Alternative Healthy Eating Index (mAHEI) with postmenopausal BC risk. Five Finnish cohorts were combined including 6374 postmenopausal women with dietary information. In all, 8–9 dietary components were aggregated in each index, higher total score i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 36 publications
(47 reference statements)
0
3
0
Order By: Relevance
“…Diet was assessed by a repeatedly validated FFQ, which has been shown to adequately measure carbohydrate fractions in our study population [ 27 ]. We assessed diet quality by the mBSDS, which is developed to measure a healthy Nordic diet, hence being appropriate for our study population [ 33 ]. The score is, however, calculated based on data-specific cut-offs, which may impair direct comparison between studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diet was assessed by a repeatedly validated FFQ, which has been shown to adequately measure carbohydrate fractions in our study population [ 27 ]. We assessed diet quality by the mBSDS, which is developed to measure a healthy Nordic diet, hence being appropriate for our study population [ 33 ]. The score is, however, calculated based on data-specific cut-offs, which may impair direct comparison between studies.…”
Section: Discussionmentioning
confidence: 99%
“…We assessed diet quality based on the modified Baltic Sea Diet Score (mBSDS), an a priori diet score developed to reflect healthy food choices in the context of a typical Nordic diet [ 33 ]. The mBSDS consists of eight score components, including cereals, fruits, vegetables, low-fat milk, fish, red and processed meat, alcohol (ethanol) and fat ratio (ratio of polyunsaturated fatty acids to saturated and trans -fatty acids).…”
Section: Methodsmentioning
confidence: 99%
“…In a study focused on the Mediterranean diet pattern, the EPIC-Greece cohort reported marginally significant inverse association with breast cancer risk among postmenopausal women (22% reduction every 2-point increase in conformity to the Mediterranean diet) [41]. This negative association resulted significant for estrogen receptor-negative (ER−) breast cancer in two studies [42,43], although, in other cohorts, no clear association has been found [44][45][46][47]. Meta-analyses including cohort studies have reported similar results, also finding inverse associations of the Mediterranean diet with breast cancer and mortality [48] and more strongly with ER− breast cancer [43,49].…”
Section: Human Data: Epidemiological Studies On the Effects Of Medite...mentioning
confidence: 99%